2018
DOI: 10.3389/fpsyt.2018.00428
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Varenicline for Smoking Cessation in Schizophrenia: A Meta-Analysis

Abstract: Objective: Smoking represents a major public health problem among patients with schizophrenia. To this end, some studies have investigated the efficacy of varenicline for facilitating smoking cessation in schizophrenia patients. The present review seeks to synthesize the results of these studies as well as document the reported side effects of using this medication.Methods: An electronic search was performed using five major databases: PubMed, Scopus, EMBASE, Web of Science, and Cochrane Library. Included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…This is likely the result of earlier reports 9 that suggested use of these medications may increase psychiatric symptoms or events in patients with SMI, however, this has subsequently been refuted. 10 In some cases, prescribing by the mental health team was required to facilitate patient access to NRT; however, this was not a sustainable alternative to a GP prescribing in the long term.…”
Section: Resultsmentioning
confidence: 99%
“…This is likely the result of earlier reports 9 that suggested use of these medications may increase psychiatric symptoms or events in patients with SMI, however, this has subsequently been refuted. 10 In some cases, prescribing by the mental health team was required to facilitate patient access to NRT; however, this was not a sustainable alternative to a GP prescribing in the long term.…”
Section: Resultsmentioning
confidence: 99%
“…While people suffering from SMI continue to smoke at higher rates than the general population, care providers often do not address nicotine addiction in this population because of the common misbelief that treatment could worsen the patient’s mental illness or that the patient lacks the motivation to quit 44. There are, however, no good quality data to support this standpoint 45. In order to increase recruitment of participants with MHDs into smoking cessation trials, it is important to clarify such misapprehensions among healthcare providers and researchers.…”
Section: Discussionmentioning
confidence: 99%
“…There may be insufficient opportunities for smoking cessation treatment and education, especially for women with schizophrenia. Smoking cessation drugs are reportedly effective and safe in assisting smoking cessation in patients with schizophrenia [37], and these medications might be easily obtained to begin immediate treatment [38]. One meta-analysis showed that the cessation rates after treatment of smoking cessation drugs were significantly higher than placebo treatment (risk ratio: 3.03–4.74) [39].…”
Section: Discussionmentioning
confidence: 99%